دابەشبونی جوگرافی بۆ خزمەتگوزاری پارکە گشتییەکان وپێداویستییەکانیان لە ئێستا و ئایندەدا لە شاری سلێمانیدا - رشید, شیروان عمر; فاتح, گەشاو فازڵ (Sulaimani Journal for Humanities, 2021)
The study was conducted to determine how to divide the geographical location of public parks in the city of Sulaymaniyah, and to determine the per capita share of public parks in current and future areas according to the population of the city. In order to achieve the main objectives of the study, first section dedicated to the geographical location of the city, the area and the population, in the second section the number, area and the geographical distribution of the public parks were determined. Then it was estimated that according to international standards, the needs of the population will depend on the per capita share of the public parks service for the years (2029-2039). The results show that although the city of Sulaymaniyah has a certain area of land in the public parks according to international standards, the per capita share (15.5m2) which is almost close to the global standard (16.2 m2), but There is also a big difference between public parks in terms of area. But there is an inequality of the distribution of public parks, with the public parks as concentrated in the northern and central parts and somewhat south of the city, and the lack of any public parks in the eastern part of the city, which is a densely populated area. The city currently needs two medium-sized public parks on the east and southwest sides. In the future, the city will need to increase the area of public parks based on three different population growth prospects (low, medium and high) for the target years (2029-2039). Efforts must be made to determine the appropriate area and location for public parks, taking into account the density and distribution of residential areas in the future, with the aim of solving the problem of unequal distribution of public parks in the city, based on an urban planning standard.